4A'S marketing strategy and bottom of pyramid populations : the case of Gua Musang, Kelantan - Wan Mohd Nazdrol Wan Mohd Nasir; An Nur Nabila Ismail (Faculty of Entrepreneurship and Business,UMK, 2015)
This is a conceptual paper to observe the alternative marketing strategy on the bottom of pyramid (BOP) population particularly at Gua Musang, Kelantan. In general, marketing strategy is associated with 4P’s; product, place, price and promotion. These elements are vital in almost any business. On the other hand, for the bottom of pyramid cases, the researcher attempts to adopt 4A’s such as affordability, awareness, access and availability instead of 4P’s. This study will be held at Gua Musang Kelantan because there are many bottom of pyramid population who stay at Gua Musang, Kelantan.